2016
DOI: 10.1016/j.ejrad.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative apparent diffusion coefficient measurement obtained by 3.0Tesla MRI as a potential noninvasive marker of tumor aggressiveness in breast cancer

Abstract: Purpose To assess the association between apparent diffusion coefficient (ADC), and histological prognostic parameters in malignant breast lesions. The ability of ADC to identify lesions with the presence of Lymphovascular invasion (LVI) in breast carcinoma was also examined. Materials and Methods This HIPAA-compliant retrospective study consisted of 212 consecutive patients with known cancers who underwent 3.0T MRI between January 2011 and 2013. In this study, a total of 126 malignant lesions in 114 women, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 32 publications
(46 reference statements)
2
32
0
Order By: Relevance
“…Several studies have evaluated ADC as a potential prognostic factor by analyzing its relationship with traditional and molecular prognostic factors, although the impact of ADC on prognosis still needs to be validated. Recently, Rabasco et al investigated the correlation between ADC in breast cancer and the presence of distant metastases at 3 years, suggesting that ADC values may represent a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have evaluated ADC as a potential prognostic factor by analyzing its relationship with traditional and molecular prognostic factors, although the impact of ADC on prognosis still needs to be validated. Recently, Rabasco et al investigated the correlation between ADC in breast cancer and the presence of distant metastases at 3 years, suggesting that ADC values may represent a significant prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…Cipolla et al (16) also revealed that the ADC values were significantly higher in G1 tumors as compared with G3 tumors, while there was no statistically significant difference upon comparison of G1 and G3 tumors with G2 tumors. By contrast, several other studies have indicated that no correlation exists between the ADC value and tumor grade (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 62%
“…The majority of previous studies (13)(14)(15)(16)(17)(18)(19)(20) have used the mean ADC value when investigating its correlation with the tumor grade. However, in the present study, the ADC min values were used instead, and significant differences were observed in these values between different tumor grades.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations